Learning Strategy for Fiqh 2 Semester 3 in the Islamic Religious Education Study Program UIN Sunan Kalijaga Yogyakarta - Fadhillah Izzatun Nisa; Radino; Sabarudin; Muh. Fauzan Hazami (al-Afkar, Journal For Islamic Studies, 2024)
The background to this research is the need for appropriate strategies in the learning process for Fiqh 2 courses. In this research, it is hoped that the results of this research can be used as parameters in implementing a strategy that is still relevant in the current context, especially in the Fiqh 2 courses at college. This research is descriptive qualitative research. The research was conducted at the Faculty of Tarbiyah Sciences, Islamic Religious Education (PAI) Study Program, UIN Sunan Kalijaga, Yogyakarta. This research is aimed only at 3rd semester students because they receive the Jurisprudence 2 course load with a weight of 4 credits for one semester in college. Data collection uses observation, interviews and documentation methods. Data analysis is carried out by processing various information that has become research data and then drawing conclusions. Data validity was checked through triangulation including sources and techniques. The results of this research show that 2nd semester fiqh lectures can be followed well by 3rd semester students through the strategies implemented by the lecturer.